General anesthesia as a possible GABAergic modulator affects visual processing in children - Van Den Boomen, Carlijn; de Graaff, Jurgen C.; de Jong, Tom P.V.M.; Kalkman, Cor J.; Kemner, Chantal (Frontiers in Cellular Neuroscience, 2013)
GABA inhibitory interneurons play an important role in visual processing, as is revealed by studies administering drugs in human and monkey adults. Investigating this process in children requires different methodologies, due to ethical considerations. The current study aimed to investigate whether a new method, being general anesthesia using Sevoflurance, can be used to trace the effects of GABAergic modulation on visual brain functioning in children. To this aim, visual processing was investigated in children aged 4-12 years who were scheduled for minor urologic procedures under general anesthesia in day care treatment. In a visual segmentation task, the difference in Event-Related Potential (ERP) response to homogeneous and textured stimuli was investigated. In addition, psychophysical performance on visual acuity and contrast sensitivity were measured. Results were compared between before and shortly after anesthesia. In two additional studies, effects at one day after anesthesia and possible effects of task-repetition were investigated. ERP results showed longer latency and lower amplitude of the Texture Negativity component shortly after compared to before anesthesia. No effects of anesthesia on psychophysical measurements were found. No effects at one day after anesthesia or of repetition were revealed either. These results show that GABAergic modulation through general anesthesia affects ERP reflections of visual segmentation in a similar way in children as benzodiazepine does in adults, but that effects are not permanent. This demonstrates that ERP measurement after anesthesia is a successful method to study effects of GABAergic modulation in children.